Variability in the step characteristics of international-level sprinters during the acceleration phase - Tugwood, R.; Bezodis, I.; Worsfold, P.; Blomkvist, B.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2018)
This study investigated within-session and across-season variability in step characteristics during maximal effort sprint accelerations of internationally competitive sprinters (n = 7) during training. Kinematic data were collected across multiple sessions over the training season. Of each adjacent four-step interval, steps 1-4 showed the highest absolute variation for step frequency, contact and flight time across the cohort, within-session. Across the season, the variability in each kinematic measure (relative to season mean) was specific to the individual, and no single technique variable fluctuated consistently with velocity. Athletes may benefit from being exposed to a variety of situational and environmental constraints that reflect the unpredictability of competition, enabling them to develop variable movement strategies whilst maintaining consistent performance levels.